If it's not what You are looking for type in the equation solver your own equation and let us solve it.
j-(-17)=30
We simplify the equation to the form, which is simple to understand
j-(-17)=30
Remove unnecessary parentheses
j+17=30
We move all terms containing j to the left and all other terms to the right.
+1j=+30-17
We simplify left and right side of the equation.
+1j=+13
We divide both sides of the equation by 1 to get j.
j=13
| 5-3*x=20 | | t+13.4=-4.5 | | 1p-5=8 | | 4(p+5)=7 | | 36t^2=9 | | -6n+5n=-3 | | 4(p+-5)=7 | | (6x-6)(4x+9)=0 | | -6r+5s+2t=-11 | | 3(x)=8.25 | | 3x^2-6x+4y^2-13=0 | | 12(y+2)=36 | | 8(x)=8.25 | | 8x+7=127 | | 170+0.25x=375 | | 7200=(756)R(2.5) | | x-8.6=4.1 | | y+5x=-10 | | -2/3+x=22/3 | | 5665*x=100000 | | 6z+17=-7 | | 12d-7+3d=19+14d | | 49x^2-10=0 | | x-.07=139500 | | -2(x-1)-4=-4(1+x)+2x+2 | | x+100=299 | | 2x-3(2x+4)=-6x+10 | | r+34=21 | | 3y+5(-3)y-3=27 | | 4u-w=u-5w | | 79/7=x-5/7 | | 420+d=-196 |